In Vitro Evaluation of the Effect of Stenting on Hematological, Hemorheological and Hemodynamic Parameters, in Various Stent Configurations and Flow Conditions - Kokkinidou, Despoina; Kapnisis, Konstantinos; Chrysostomou, M.; Shammas, Christos; Anayiotos, Andreas; Kaliviotis, Efstathios (My University, 2025)
Percutaneous coronary intervention is used extensively for the restoration of blood flow in diseased arteries. The influence of stent implantation on the physiology and flow of blood is an important and still not fully understood issue. The current work evaluated possible stent-induced changes in hematological, hemorheological and hemodynamic parameters.
Keywords: Stents; Hematology; Hemodynamics; Hemorheology; Pressure-drop; Red blood cell biomechanics; Stent-induced changes